Influence of Adding a Convex Lens as a Solar Concentrator on the Performance of Solar Cooker with an octagonal panel: Nurul Amalia Silviyanti Siswoyo and Rinaldy Harjo Purnomo - Nurul Amalia Silviyanti Siswoyo Nurul Amalia Silviyanti Siswoyo; Rinaldy Harjo Purnomo Rinaldy Harjo Purnomo (Jurnal Fisika dan Aplikasinya, 2023)
Currently, the two most popular renewable energy is solar power and wind power. However, solar power can be harvested almost in every region for a whole year during the day because Indonesia is located at the equator with average daily radiation of 4,8 kWh/m2. One way to use solar power is used in a solar cooker. The octagonal solar cooker is combine of box type solar cooker and panel type solar cooker. The box part is made of a zincalume with a half-cylinder shape as a reflector from the octagonal reflector to the cooking tray. An addition of convex lens put under the cooking tray. In each cooking tray, 500 mL of water was placed, and the sun's radiation heated the water. Performance of solar cooker tested at 09.00 in the morning for two and half hour or 180 minute . The results show that adding four convex lenses improved the solar cooker's performance, allowing the highest temperature to rise to 86 °C and increasing efficiency to 15.9%. In comparison to an addition, only one convex lens raises the temperature to 84,3 °C with a 15.4% efficiency, while the temperature without the lens rises to 70 °C with an 11.4% efficiency.